Thermal analysis of a double-glazing window using a Nano-Disbanded Phase Changing Material (NDPCM). (2022) - Kaushik, Nitish; Saravanakumar, P.; Dhanasekhar, S.; Saminathan, Rajasekaran; Rinawa, Moti Lal; Subbiah, Ram; Sharma, Rajneesh; Manoj Kumar, P.
Abstract: Building energy consumption is playing a key role in global energy demand. The previous researches demonstrated that the type and material of the windows influences the building energy consumption. The present study experimentally examines the heat transfer characteristics of a double-glazing window system which is united with a Nano-Disbanded Phase Changing Material (NDPCM) and the results are analyzed by comparing it with a window with the normal PCM and a standard double-glazing unit. The NDPCM had been synthesized beforehand through the dispersion of 1.0 vol fraction of nano-silica (SiO2 ) within the technical grade paraffin. The interior thermal environment, inside temperature of the window glass, consumed energy via glazed windows, and glass transmittance with NDPCM were all critically evaluated. The results demonstrated that the transmittance of the window unit with NDPCM was sufficient enough throughout the day to permit adequate sun-light into the experimented space. Additionally, the NDPCM diminished the interior glass-panel temperature by 8.5 °C, abridged temperature variability of the investigated space by 5.5 °C, and enhanced energy conservation by 4.61%.